Exploring Research Capacity and Capacity Building Needs Among Faculty Members and Personnel of AIMS: Inputs for Effective Research Training Plan for AIMS - Cabasal, Maria Celia; Escalona, Jessa B. (International Journal of Multidisciplinary: Applied Business and Education Research, 2023)
This study focused on assessing the research capacity and capacity-building needs of faculty members and personnel at the Asian Institute of Maritime Studies (AIMS) to enhance the institution's research culture. The study revealed that AIMS has lagged in terms of research production. To overcome this challenge, the Center for Research and Institutional Development (CRID) at AIMS has developed research programs and training to cultivate a research-oriented environment. Using a descriptive correlational design, the study involved 167 faculty members and personnel. Three domains were assessed: individual, team, and organization. A questionnaire comprising three parts was utilized for data collection. The first part aimed to gather respondents' profiles, while the second part contained statements pertaining to research capacity assessment in the three domains. The third part addressed research capacity-building needs and the available resources at AIMS. The results indicated that respondents possessed a basic understanding and capabilities in research, as reflected in their average weighted mean scores. They also identified research funding, facilities and infrastructures, research training, and support for presentation and publication as vital components for successful research endeavors. Furthermore, the study established a strong relationship between research capacity assessment and the need for funding, facilities/infrastructure, training, and presentation/publication support. Higher research capacity assessment scores correlated with greater capacity-building needs across the three domains. Consequently, the study recommended that the CRID office should assess the research-level capabilities of faculty members and personnel and provide targeted research training to address their specific needs.